A study of leisure activities of young people / Chen Ka Foo - Chen , Ka Foo (1980)
This study attempts to investigate the leisure activities of young people and to see their range of leisure, whether there is any occupational and sex differences in the choice of leisure. A total of 40 respondents, comprising 20 clerks and 20 Sixth Form students, males and females ranging between the age of 18 to 24 years were interviewed. In addition, three officers of the Ipoh Municipal Council were interviewed to obtain information regarding leisure provision and planning in Ipoh town. The findings of this study generally showed that leisure activities of respondents are basically home-oriented. Analysis of the results shows that more men than women are engaged in physical and social leisure activities, while practical and intellectual activities are more popular with women. Both clerks and students are most preoccupied with social leisure activities, and that intellectual activities is least popular with clerks. Respondents are generally satisfied with the available leisure facilities and their present leisure activities.